Political detainees ; New hope for Bacolor ; Music borders [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Tackles unaanswered justice for political detainees. The Pinatubo victims continue to rebuild their homes and living a normal life. Peter Loro playing trumpet with one hand and Sarah, a cellist using corrugated plastic hoses as instruments makes music in classical way.